2015
DOI: 10.3399/bjgp16x683161
|View full text |Cite
|
Sign up to set email alerts
|

Persistent problems 1 year after mild traumatic brain injury: a longitudinal population study in New Zealand

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
139
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 193 publications
(175 citation statements)
references
References 31 publications
(38 reference statements)
9
139
3
Order By: Relevance
“…Recent inception cohort studies suggest that at least 1 in 5 patients with mTBI will experience symptoms that persist for longer than 1 month 17,18,20,74,75 and that recovery is frequently complicated by preexisting and comorbid health conditions. 58,76,77 Children return to school after a median of 2-4 days 78 and the median return to work time for adults is 1-2 weeks, 79 although 1 in 5 adults remain off work at 6 months post injury.…”
Section: Prognosismentioning
confidence: 99%
“…Recent inception cohort studies suggest that at least 1 in 5 patients with mTBI will experience symptoms that persist for longer than 1 month 17,18,20,74,75 and that recovery is frequently complicated by preexisting and comorbid health conditions. 58,76,77 Children return to school after a median of 2-4 days 78 and the median return to work time for adults is 1-2 weeks, 79 although 1 in 5 adults remain off work at 6 months post injury.…”
Section: Prognosismentioning
confidence: 99%
“…Prevalence is slightly higher (14.3%) among New Zealand (NZ) males aged 35-39 years [2]. Following a TBI, people can experience long-term cognitive and emotional difficulties that affect every day functioning, decision making, social relationships and employment [3,4,5,6]. Additionally, there is evidence of a relationship between TBI and increased dysregulated behaviours such as impulsivity and aggression, mood disturbances and substance abuse and psychiatric conditions and [7] a link between a history of TBI and engagement in antisocial or criminal behaviour has been proposed [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…[9]. Multiple researchers suggested integrated biopsychosocial approaches for future studies to best explain the outcome of TBI [80][81][82][83]. However, few studies have yet examined identified biopsychosocial factors in a comprehensive model over time to determine the significant underlying factors that contribute to post-TBI fatigue and sleep problems.…”
Section: Discussionmentioning
confidence: 99%